KINERJA KEPOLISIAN BIDANG NARKOBADALAM MENINDAK KURIRDAN PENGGUNA NARKOBADI KELURAHANSIMBAWARINGIN KECAMATAN TRIMURJO KABUPATEN LAMPUNG TENGAH - Widodo, Wahyu (Jurnal Analisis Sosial Politik, 2021)
This study aims to analyze the performance of the Police in the Narcotics Sector in cracking down on Couriers and Drug Users in Simbawaringin Village, Trimurjo District, Central Lampung Regency. The type of research used is descriptive research with a qualitative approach. narcotics and psychotropic substances. Besides that, what is very important is the need for legal awareness from all levels of society in order to uphold the authority of the law. In today's developments, the Indonesian people demand that the National Police be an institution that is humanist, professional and upholds human rights and is able to create social justice in the community. Satnarkoba members are given the opportunity to excel by developing the best ideas in reducing and taking action against users and dealers. Drugs in Trimurjo District, Central Lampung Regency. members of the Central Lampung POLRES Satnarkoba have the opportunity to show their work performance on duty, because there is indeed an assessment given, members of the Satnarkoba are given the opportunity to excel by developing the best ideas in reducing and taking action against drug users and dealers in Trimurjo District, Central Lampung Regency . Keywords: Police performance, drugs, courier